Penyuluhan dan Pelatihan Pembuatan Plant Growth Promoting Rhizobacteria (PGPR) di Desa Depokrejo, Kecamatan Kebumen, Kabupaten Kebumen - Chalisty, Vian Dwi; Sudiro, Fiki; Fatimah, Ismi Widiyanti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The majority of farmers in Depokrejo Village, Kebumen District, Kebumen Regency, Central Java Province still rely on inorganic chemical fertilizers. While these fertilizers quickly provide the necessary nutrients for plants, their continuous use poses a threat to soil and the environment. A more sustainable and cost-effective alternative is biological fertilizer, which contains microbial inoculants to support plant growth. One such option that is relatively unknown to farmers is using bamboo roots as biological fertilizers to replace inorganic chemical fertilizers. We conducted a community service activity to educate and equip farmers in Depokrejo Village with the knowledge and skills to produce Plant Growth Promoting Rhizobacteria (PGPR) biological fertilizers using bamboo roots. The methods employed in this activity included field surveys, discussions, socialization, and training on PGPR production. Community service activities commenced with field surveys and discussions involving village officials, RT/RW officials, and the community. The initiative continued with the compilation of a work program and the determination of the time and location for the activities. Socialization and training were conducted on the same day. The materials used to create PGPR include bamboo roots, shrimp paste, granulated sugar, bran, and water. The farmers' increased enthusiasm and active participation in meetings, Q&A sessions, and PGPR production demonstrate their improved understanding and skills in using PGPR biofertilizer. By encouraging farmers to produce and use PGPR on agricultural land independently, we aim to reduce their reliance on inorganic chemical fertilizers and promote environmental sustainability